Potential Effectiveness of Chinese Patent Medicine Tongxinluo Capsule for Secondary Prevention After Acute Myocardial Infarction: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Min; Li, Chengyu; Chen, Shiqi; Sun, Yang; Hu, Jiayuan; Zhao, Chen; Qiu, Ruijin; Zhang, Xiaoyu; Zhang, Qin; Tian, Guihua; Shang, Hongcai (Frontiers in Pharmacology, 2018)
ABSTRACT Background. Chinese patent medicine Tongxinluo capsule (TXL) is commonly used for cardio-cerebrovascular diseases. Previous research had demonstrated that TXL exhibited great clinical effects on the treatment of acute myocardial infarction (AMI), however there is a lack of systematic review. The purpose of this study was to evaluate the potential effectiveness and safety of TXL for secondary prevention in patients with AMI. Method. We searched six databases to identify relevant randomized controlled trials (RCTs) from inceptions to December 30, 2017. Two review authors independently assessed the methodological quality and analyzed data by the RevMan 5.3 software. The publication bias was assessed through funnel plot and Begg’s test. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used for evaluating the quality of evidence. Results. We included nineteen RCTs in this review and performed a meta-analysis based on sixteen studies. There were statistical differences of TXL treatment group in reducing primary cardiovascular events (cardiac death [RR=0.27, 95% CI: 0.08~0.95, I2=0%], recurrent myocardial reinfarction [RR=0.38, 95%CI: 0.20~0.74, I2=0%], arrhythmia [RR=0.44, 95%CI: 0.30~0.66, I2=0%], recurrent angina pectoris [RR=0.34, 95%CI: 0.17~0.69, I2=0%]). TXL could improve cardiac function (LVEF [MD=4.10, 95%CI: 3.95~4.25, I2=0%]), regulate blood lipid (TC [MD=-0.66, 95%CI: -0.94~-0.37, I2=74%], TG [MD=-0.38, 95%CI: -0.62~-0.14, I2=70%], LDL-C[-0.40, 95%CI: -0.65~-0.16, I2=88%), decrease the level of hs-CRP (4-week: MD=-0.78, 95%CI: -0.97 ~-0.60, I2=20%; Over 4-week: MD=-1.36, 95%CI: -1.55 ~-1.17, I2=20%). However, TXL has little effects on revascularization [RR=0.45, 95%CI: 0.13~1.56, I2=0%], recurrent heart failure (RR=0.83, 95%CI: 0.27~2.57, I2=0%), and HDL-C (MD=0.14, 95%CI: 0.00 ~0.29, I2=73%). Furthermore, TXL treatment group was more prone to suffer gastrointestinal discomfort. Conclusion. Chinese patent medicine TXL seemed beneficial for secondary prevention after AMI. This potential benefit needs to be further assessed through more rigorous RCTs.